The investigation of samples containing many species: I. Sample description - Bullock, J.A. (Oxford University Press, 1971)
The examination of samples containing many species presents difficulties of description and comparison when the samples are treated as entities. Five different methods of sample description are discussed with special reference to mist‐net samples of Malayan birds and it is concluded that the log‐series is the most satisfactory with these data. The variation of the index of diversity is examined in time and between habitats and it is concluded that the index provides a measure of habitat diversity in relation to a fauna but may be affected by lack of species preadapted to newly available or expanded habitats. Theoretical and practical features of the various models are also examined. Copyright © 1971, Wiley Blackwell. All rights reserved